A Fresh Look at Systems Engineering – What is it, How Should it Work?. Issue 3 (14th November 2018) - Sillitto, Hillary; Martin, James; Griego, Regina; McKinney, Dorothy; Arnold, Eileen; Godfrey, Patrick; Dori, Dov; Krob, Daniel; Jackson, Scott
ABSTRACT: INCOSE's definition of systems engineering was compared to the aspirations set out in the INCOSE Systems Engineering Vision 2025 for systems engineering as it ought to be to address modern challenges. Doing this led us to three fundamental realisations. First, while "20th century systems" were, for the most part, "deterministic" or nearly so, 21st century systems are on the other hand increasingly non‐deterministic, adaptive or "evolutionary." Second, while "20th Century systems engineering management" was implicitly based on a "command and control" paradigm, 21st Century systems engineering, to be successful, will usually need to use a more collaborative leadership paradigm. And third, that while 20th Century systems were largely "single systems", designed to "solve" specific problems, 21st Century systems are almost invariably networked, and are parts of complex extended enterprises with multiple, often conflicting, stakeholder objectives, that are intimately related to complex societal challenges. We used elements of soft systems methodology (SSM) to understand the implication and consequences of the paradigm shift implied by these realisations. A revised strawman definition of systems engineering is offered for consideration by INCOSE, showing the changes that would be required to take these and related factors into account.